Construction of a Morphing Wing Rib Actuated by a NiTi Wire - Thais Campos de Almeida; Osmar de Sousa Santos; Jorge Otubo (Journal of Aerospace Technology and Management, 2015)
The main goal of this paper is to analyze if it is feasible to employ a trained shape memory alloy wire as a linear actuator to modify the camber of a morphing wing rib. In order to achieve this purpose, a morphing rib with a compliant trailing edge was proposed, developed, and subjected to structural analyses to ensure its flexibility. After the rib configuration was set, it was manufactured by a 3-D printer. The NiTi wire used as actuator was trained by a thermomechanical procedure based on a cycling process with a constant load application to present the two-way shape memory effect. In that way, the wire presents a determined length at its low-temperature phase and a shorter one at its high-temperature phase. Since the wire contraction and the torque applied by it are two crucial factors to define the camber curvature, it was decided to study two different wire lengths: 103.5 and 152.1 mm. The aerodynamic performance of the morphing cambered airfoils was studied using XFOIL software and compared to that of conventional airfoils with single hinged flap. The results show that both morphing airfoils present better aerodynamic performance for small angles of attack.